Progression characteristics of the European Friedreich's Ataxia Consortium for Translational Studies (EFACTS): a 4-year cohort study. Issue 5 (May 2021) - Reetz, Kathrin; Dogan, Imis; Hilgers, Ralf-Dieter; Giunti, Paola; Parkinson, Michael H; Mariotti, Caterina; Nanetti, Lorenzo; Durr, Alexandra; Ewenczyk, Claire; Boesch, Sylvia; Nachbauer, Wolfgang; Klopstock, Thomas; et al.
Summary: Background: The European Friedreich's Ataxia Consortium for Translational Studies (EFACTS) investigates the natural history of Friedreich's ataxia. We aimed to assess progression characteristics and to identify patient groups with differential progression rates based on longitudinal 4-year data to inform upcoming clinical trials in Friedreich's ataxia. Methods: EFACTS is a prospective, observational cohort study based on an ongoing and open-ended registry. Patients with genetically confirmed Friedreich's ataxia were seen annually at 11 clinical centres in seven European countries (Austria, Belgium, France, Germany, Italy, Spain, and the UK). Data from baseline to 4-year follow-up were included in the current analysis. Our primary endpoints were the Scale for the Assessment and Rating of Ataxia (SARA) and the activities of daily living (ADL). Linear mixed-effect models were used to analyse annual disease progression for the entire cohort and subgroups defined by age of onset and ambulatory abilities. Power calculations were done for potential trial designs. This study is registered with ClinicalTrials.gov, NCT02069509 . Findings: Between Sept 15, 2010, and Nov 20, 2018, of 914 individuals assessed for eligibility, 602 patients were included. Of these, 552 (92%) patients contributed data with at least one follow-up visit. Annual progression rate for SARA was 0·82 points (SE 0·05) in the overall cohort, and higher in patients who were ambulatory (1·12 [0·07]) than non-ambulatory (0·50 [0·07]). ADL worsened by 0·93 (SE 0·05) points per year in the entire cohort, with similar progression rates in patients who were ambulatory (0·94 [0·07]) and non-ambulatory (0·91 [0·08]). Although both SARA and ADL showed slightly greater worsening in patients with typical onset (symptom onset at ≤24 years) than those with late onset (symptom onset ≥25 years), differences in progression slopes were not significant. For a 2-year parallel-group trial, 230 (115 per group) patients would be required to detect a 50% reduction in SARA progression at 80% power: 118 (59 per group) if only individuals who are ambulatory are included. With ADL as the primary outcome, 190 (95 per group) patients with Friedreich's ataxia would be needed, and fewer patients would be required if only individuals with early-onset are included. Interpretation: Our findings for stage-dependent progression rates have important implications for clinicians and researchers, as they provide reliable outcome measures to monitor disease progression, and enable tailored sample size calculation to guide upcoming clinical trial designs in Friedreich's ataxia. Funding: European Commission, Voyager Therapeutics, and EuroAtaxia.